2011
DOI: 10.3182/20110828-6-it-1002.02725
|View full text |Cite
|
Sign up to set email alerts
|

Planning transport sequences for flexible manufacturing systems*

Abstract: When designing a manufacturing system it is important to plan what the system should do. One important activity in most manufacturing systems is to transport products or resources between different positions. In a flexible manufacturing system it can be challenging to design and plan these transport operations due to their complex logical behavior. This paper presents a method that identifies, creates and visualizes these transport operations based on inputs from a standard virtual manufacturing tool and a hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…This benchmark concerns a fabrication production system that can build different products [35]. There exist two product families, each one consisting of two product types.…”
Section: ) Fabrication Production System (Fbs)mentioning
confidence: 99%
“…This benchmark concerns a fabrication production system that can build different products [35]. There exist two product families, each one consisting of two product types.…”
Section: ) Fabrication Production System (Fbs)mentioning
confidence: 99%
“…different resources or products can be displayed by using a projection of operations that somehow relates to that resource or product. Recently, it has been shown that transport operations can be automatically generated from simulation software [8]. The next step is to also generate process operations based on the product recipe from external CAD software.…”
Section: Operation Relationsmentioning
confidence: 99%
“…This tool provides a bridge between other simulation languages, formal language verification tools and PLC code generation. Magnusson et al (2011) proposes a method for generating the sequences of operation in SPL directly from a virtual environment.…”
Section: Sequence Planner Languagementioning
confidence: 99%
“…Comparing the methodologies of SysML and SPL, clarifies the representation of the specification of the model in each respective language. The methodology for modeling a system in SPL begins by obtaining the information from a simulation tool or a design tool, continues by forming the sequences of operations of the process, see Magnusson et al (2011). The specification, or requirement is also defined as a model in the Sequence Planner tool, either by defining a resource and its particulars, or by defining the specification of other necessities.…”
Section: Formal Verificationmentioning
confidence: 99%